Validity evidence for a sentence repetition test of Swiss German Sign Language. (July 2020) - Haug, Tobias; Batty, Aaron Olaf; Venetz, Martin; Notter, Christa; Girard-Groeber, Simone; Knoch, Ute; Audeoud, Mireille
In this study we seek evidence of validity according to the socio-cognitive framework (Weir, 2005) for a new sentence repetition test (SRT) for young Deaf L1 Swiss German Sign Language (DSGS) users. SRTs have been developed for various purposes for both spoken and sign languages to assess language development in children. In order to address the need for tests to assess the grammatical development of Deaf L1 DSGS users in a school context, we developed an SRT. The test targets young learners aged 6–17 years, and we administered it to 46 Deaf students aged 6.92–17.33 ( M = 11.17) years. In addition to the young learner data, we collected data from Deaf adults ( N = 14) and from a sub-sample of the children ( n = 19) who also took a test of DSGS narrative comprehension, serving as a criterion measure. We analyzed the data with many-facet Rasch modeling, regression analysis, and analysis of covariance. The results show evidence of scoring, criterion, and context validity, suggesting the suitability of the SRT for the intended purpose, and will inform the revision of the test for future use as an instrument to assess the sign language development of Deaf children.